Information Visualization of Lesson Study Activity - Mardhia, Murein; Azhari, Ahmad; Ardiansyah, Ardiansyah (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2017)
This research explores how to design an interface dashboard to visualize information about evaluation activities occurred during lesson study. Data were collected in two stages using interview and questionnaire techniques whom the respondents were experts and team teaching who had been experienced the whole activities of Lesson Study. We conducted a case study in Mathematics Education Program of Universitas Ahmad Dahlan, where the teaching staffs have participated and conducted the Lesson Study activities for more than two semesters. The interface dashboard prototype was tested by conducting User Experience method and Software Usability Testing assessment. Results obtained show a fairly good acceptance level qualitatively and so does from SUS scored 75 from the average value of all participants